Foucault, San Jerónimo, y la mujer fatal: apropiación y subversión de la iconografía religiosa en El espíritu de la colmena de Víctor Erice. - Jerez-Farràn, Carlos (Hispanic Research Journal, 2014)
This article examines the symbolic value of one of the paintings in Victor Erice's acclaimed El espíritu de la colmena that has caused much perplexity among its commentators: that of the patriarch Saint Jerome we see presiding Fernando's study room and is later on associated with his daughter Isabel through the short and medium shots the camera takes to contrast the ascetic saint and the child's sexually provocative lips. The implications of vampirism and fellatio this feminine 'perverse' and proto-'monster' child forebodes is conceived as a counter- discourse Erice erects against those conservative and repressive institutions that the film suggests through the association of Fernando and the Patriarch. The purpose of this montage is to rethink Francoist morality and imply that the moral, social, and psychological values of post-war Spain were based on the same misogynous and erotophobic prejudices that were handed down from the biblical, mythological, historical, and cultural past that the ascetic personifies. In this sense, the religious legacy Franco deployed during the post-war years is appropriated to suggest the genesis of the false religious, political, and ideological demi-gods Spain erected during that long chronicle of repression that Franco's dictatorship enforced. It forebodes at the same time the return of the repressed that Isabel's attitudes symbolizes.